Accuracy of Kampala Trauma Score as a Predictor in Assessing the Prognostic Value of Multiple Trauma - Usman, Nurhayat; Ruchimat, Tommy; Rahmawan, Andhika (Majalah Kedokteran Bandung, 2023)
Determining a trauma scoring system appropriate for certain conditions will help in predicting mortality and morbidity, and can determine the need for treatment in patients. Kampala Trauma Score (KTS) is a trauma scoring system that uses a decent number of assessment variables and can be used in all general groups. This study was a retrospective prognostic test conducted in Dr. Hasan Sadikin Hospital Bandung, Indonesia, from December 2021 to July 2022. Data obtained was processed using Microsoft Excel and SPSS spreadsheets. The respondents were 66 people with multiple trauma. Results showed that this study was dominated by patients with blunt trauma  (n=63, 95.45%). The mean KTS score in this study was 13.08±1.03. In 49 (74.24%) patients who survived, the mean KTS score was 13.41±0.89 and in 17 (25.76%) patients who died, the mean KTS score was 12.12±0.79. The greatest mortality accuracy was at the cutoff point of the KTS score >12 (81.82% accuracy; 70.59% sensitivity; 85.71% specificity). The accuracy value of the KTS score is in line with the ROC where the optimal KTS score is >12 (85.77%). In conclusion, the Kampala trauma score can be used as a predictor in assessing the prognostic value of multiple trauma patients with the obtained cut-point value as it has high accuracy, sensitivity, and specificity values.